2012
DOI: 10.1111/j.2042-3306.2012.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of serum anti‐Müllerian hormone concentrations for the diagnosis of granulosa‐cell tumours in mares

Abstract: Measurement of serum AMH concentrations can be used for diagnosis of GCTs in the mare. As serum AMH concentrations do not vary significantly during the oestrous cycle or pregnancy, interpretation of these results is not confounded by these physiological states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 28 publications
1
65
1
1
Order By: Relevance
“…Anti‐Müllerian hormone has been recently reported as a diagnostic marker for GCT in mares (Ball et al . , ; Almeida et al . ) but an assay for this hormone was not available at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti‐Müllerian hormone has been recently reported as a diagnostic marker for GCT in mares (Ball et al . , ; Almeida et al . ) but an assay for this hormone was not available at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, anti‐Müllerian hormone has been reported as a diagnostic marker for GCT (Ball et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, in mares, it was found that the sensitivity of anti-Müllerian hormone (AMH) for detection of GCTs was significantly higher than that of either inhibin or testosterone (Ball et al 2013). Similarly, in cattle, the measurement of plasma AMH concentration was identified as a more reliable and sensitive method to diagnose GCTs than that of the measurement of INH or ovarian steroids (Kitahara et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In mares, testosterone and inhibin assays have been utilised to enhance non-surgical ante-mortem diagnosis (McCue et al 2006). More recently AMH has been used as a highly sensitive and specific assay in both mares (Ball et al 2008(Ball et al , 2013 Lactogenesis in the absence of pregnancy has previously been reported in a ewe with GTCT (Gardner et al 2005). There are several reports of transient lactogenesis associated with GTCT in dairy cattle (Short et al 1963;Whitacre et al 1988;Palmer et al 2005), and in dairy cows transported by boat (Mansell et al 2014).…”
Section: Spontaneous Lactogenesis and Galactopoeisis In A Virgin Dairmentioning
confidence: 99%